2008
DOI: 10.1016/j.jns.2008.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mitochondrial encephaloneuromyopathy due to a defect of mitochondrial protein synthesis

Abstract: Mitochondrial diseases are clinically and genetically heterogeneous disorders due to primary mutations in mitochondrial DNA (mtDNA) or nuclear DNA (nDNA). We studied a male infant with severe congenital encephalopathy, peripheral neuropathy, and myopathy. The patient's lactic acidosis and biochemical defects of respiratory chain complexes I, III, and IV in muscle indicated that he had a mitochondrial disorder while parental consanguinity suggested autosomal recessive inheritance. Cultured fibroblasts from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…One possibility is that Msc6p improves the stringency with which mIF-2 positions the fMet-tRNA fMet on the mRNA and the ribosomal small subunit. Despite the well-known consequences of mitochondrial translation impairments in human diseases [8,39,40], a recent study also unveiled that mitochondrial translation accuracy directly affects the proteostatic capacity of the cytoplasm as well as coordinates nuclear stress signaling and cellular life span [22]. Here we showed that msc6 and ifm1 mutants present low viability in two different longevity/survival assays in agreement with some recent data [22] but distinct from others mitochondrial translational factors mutants [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that Msc6p improves the stringency with which mIF-2 positions the fMet-tRNA fMet on the mRNA and the ribosomal small subunit. Despite the well-known consequences of mitochondrial translation impairments in human diseases [8,39,40], a recent study also unveiled that mitochondrial translation accuracy directly affects the proteostatic capacity of the cytoplasm as well as coordinates nuclear stress signaling and cellular life span [22]. Here we showed that msc6 and ifm1 mutants present low viability in two different longevity/survival assays in agreement with some recent data [22] but distinct from others mitochondrial translational factors mutants [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…These disorders are generally multisystemic [6, 8] and may be present at any age [7], and the global prevalence, probably underestimated, is 1/8500 [7]. The organs with highest energy demand, such as, heart, brain, skeletal muscle tissue, and liver, are preferentially involved [6, 8–11].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial disorders are a heterogeneous group of diseases characterized by defects of mitochondrial structure and oxidative phosphorylation [ 6 – 8 ]. These disorders are generally multisystemic [ 6 , 8 ] and may be present at any age [ 7 ], and the global prevalence, probably underestimated, is 1/8500 [ 7 ]. The organs with highest energy demand, such as, heart, brain, skeletal muscle tissue, and liver, are preferentially involved [ 6 , 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that patients with mutations in the RMND1 gene present impaired mitochondrial translation [68][69][70]. Defective RMND1 lead to lower steady state level of ribosome subunits MRPL13, MRPL32, MRPS2, as well as lower content of 16S rRNA indicating a role for RMND1 in the assembly or maintenance of mitochondrial ribosome [68,70].…”
Section: Ribosome Biogenesis and Proteinsmentioning
confidence: 99%